2010
DOI: 10.4103/0019-5049.65366
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ASA classification and ACE-27 index as morbidity scoring systems in oncosurgeries

Abstract: The primary intention of the study was to find out whether Adult Comorbidity Evaluation Index (ACE-27) was better than the American Society of Anaesthesiologists’ (ASA) risk classification system in predicting postoperative morbidity in head and neck oncosurgery. Another goal was to identify other risk factors for complications which are not included in these indexes. Univariate and multivariate analyses were performed on 250 patients to determine the impact of seven variables on morbidity-ACE-27 grade, ASA cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Various studies reported that patients with positive neck nodes have worse prognosis . Also, ASA scores have been reported to be predictive for morbidity and mortality as well as chance for successful organ preservation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies reported that patients with positive neck nodes have worse prognosis . Also, ASA scores have been reported to be predictive for morbidity and mortality as well as chance for successful organ preservation …”
Section: Discussionmentioning
confidence: 99%
“…18,24 Also, ASA scores have been reported to be predictive for morbidity and mortality as well as chance for successful organ preservation. [25][26][27] Next to survival, quality of life, toxicity, and larynx preservation are important parameters in the decisionmaking process. Both organ sacrificing and preserving treatments for advanced laryngeal cancer significantly affect quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Stress of surgery and anaesthesia can induce various metabolic and endocrine changes, such as hypothermia, hypovolaemia, tissue hypoperfusion, leading to greater postoperative morbidity, including wound infection and delayed healing . Duration of general anaesthesia has been confirmed to be a significant factor in increasing complications, with anaesthesia time greater than 8 h found to be an independent predictor of postoperative morbidity …”
Section: Discussionmentioning
confidence: 99%
“…8,9 Duration of general anaesthesia has been confirmed to be a significant factor in increasing complications, with anaesthesia time greater than 8 h found to be an independent predictor of postoperative morbidity. 7,10 Co-morbidity has been found to have a significant impact on treatment selection, LOS, postoperative complications and survival in several types of malignancies, including head and neck cancer. 11 Interestingly, our study showed no significant correlation between ACE-27 index grades 2 and 3 and LOS.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…On univariate analysis, comorbidity indicies, namely the Adult Comorbidity Evaluation (ACE-27) and the American Society of Anesthesiologists' (ASA) scores, are associated with perioperative risk and this has been corroborated by other recent publications. 22,23 Further investigation of data is likely to result in one or more of these scores being included in an updated risk adjustment model for head and neck surgery. Laryngeal operations, when singled out as an anatomical site, added significantly to risk.…”
Section: Discussionmentioning
confidence: 99%